Perbandingan Aktivitas Antibakteri Ekstrak Etanol Bunga Brokoli (Brassica oleracea var. italica Plenck) dan Kembang Kol (Brassica oleracea var. botrytis DC.) terhadap Propionibacterium acnes - salsabila soedradjat; Livia Syafnir; Indra Topik Maulana (Bandung Conference Series: Pharmacy, 2022)
Abstract. Acne is a skin disease that often occurs in all circles that causes inflammation. The main cause of acne is the bacteria Propionibacterium acnes. This study aims to compare the antibacterial activity ethanol extract of broccoli flower and ethanol extract of cauliflower to the acne-causing bacteria P. acnes measured from the diameter of the resulting inhibition zone, as well as to compare the parameters and characteristics of each materials. The study began with standard parameter determination test, then phytochemical screening and antibacterial activity test for P. acnes. The results showed that broccoli contains alkaloids, flavonoids, phenolic compounds, tannins, quinones, saponins, steroids, monoterpenes and sesquiterpenes. Cauliflower contains alkaloids, flavonoids, phenolic compounds, tannins, quinones, saponins, steroids, triterpenoids, monoterpenes and sesquiterpenes. The results of the comparison test of antibacterial activity of ethanol extract broccoli flower and ethanol extract cauliflower to P. acnes with test concentrations of 1%, 5%, 10%, 15% and 20% using the well method showed negative results, where the two ingredients were not able to inhibit the growth rate of bacteria P. acnes. In the positive control, namely clindamycin, which showed an average diameter of the inhibition zone of 32.65 mm, the antibiotic produced antibacterial activity against the growth of P. acnes. This could be due to the fact that the two extracts were not active at all as antibacterial P. acnes, but had other antibacterial activities. Abstrak. Jerawat adalah penyakit kulit yang sering terjadi pada semua kalangan yang menyebabkan inflamasi. Penyebab utama terjadinya jerawat adalah bakteri Propionibacterium acnes. Penelitian ini bertujuan untuk membandingkan aktivitas antibakteri antara ekstrak etanol bunga brokoli dengan ekstrak etanol kembang kol terhadap bakteri penyebab jerawat P. acnes diukur dari diameter zona hambat yang dihasilkan, serta untuk membandingkan parameter dan karakteristik dari masing-masing bahan. Penelitian diawali dengan uji penetapan parameter standar lalu penapisan fitokimia dan dilakukan uji aktivitas antibakteri terhadap P. acnes. Hasil penelitian menunjukkan bahwa pada brokoli mengandung senyawa alkaloid, flavonoid, fenolik, tanin, kuinon, saponin, steroid, monoterpen dan seskuiterpen. Pada kembang kol mengandung senyawa alkaloid, flavonoid, fenolik, tanin, kuinon, saponin, steroid, triterpenoid, monoterpen dan seskuiterpen. Hasil uji perbandingan aktivitas antibakteri ekstrak etanol bunga brokoli dan kembang kol terhadap P. acnes pada konsentrasi uji 1%, 5%, 10%, 15% dan 20% menggunakan metode sumuran menunjukkan hasil negatif, dimana kedua bahan tersebut tidak mampu menghambat laju pertumbuhan dari bakteri P. acnes. Pada kontrol positif yaitu klindamisin menunjukkan rata-rata diameter zona hambat sebesar 32,65 mm maka antibiotik tersebut menghasilkan aktivitas antibakteri terhadap pertumbuhan P. acnes. Hal tersebut dapat disebabkan karena kedua ekstrak tidak aktif sama sekali sebagai antibakteri P. acnes, melainkan aktivitas antibakteri lain.